Prophylactic pancreatic duct stenting in severe acute necrotizing pancreatitis: a prospective randomized study - Karjula, Heikki; Nordblad Schmidt, Palle; Mäkelä, Jyrki; Liisanantti, Janne H.; Ohtonen, Pasi; Saarela, Arto (Endoscopy, 2019)
Background Pancreatic duct disruption is common and is associated with high morbidity in cases of acute necrotizing pancreatitis (ANP). In this study, we tested the feasibility and safety of prophylactic pancreatic duct stenting (PPDS) in ANP and compared PPDS with conservative treatment.Methods We prospectively enrolled patients (aged 18 – 75 years) diagnosed with ANP between February 2011 and July 2015. These patients were prospectively randomized to receive PPDS or conservative treatment at two tertiary centers. PPDS was performed as soon as possible after randomization. Results Concern regarding iatrogenic infections with pancreatic necrosis in the PPDS group prompted interim analysis, which confirmed a highly elevated risk. Thus, the trial was terminated prematurely for ethical reasons. Of the 11 patients in the PPDS group, all patients with successful pancreatic duct placement (5/5, 100 %) presented with infection, compared with only 3 of the 13 patients (23.1 %) in the conservative treatment group (P = 0.01). Analysis revealed success rates of 63.6 % for pancreatic duct cannulation, 45.5 % for pancreatic duct stenting, and 18.2 % for placement of a stent bridging the necrosis. Cannulation and stenting failures were due to duodenal edema and pancreatic duct stenosis.Conclusions PPDS in ANP is associated with an unacceptably high risk of pancreatic necrosis infection. In addition, the procedure is technically challenging due to duodenal edema and ductal stenosis.